Network design, modeling and performance evaluation - Vien, Quoc-Tuan (IET telecommunications series, 2018)
The book is written at postgraduate level and comprises N chapters dealing with the following subjects: internetworking; network fundamentals; routing; computer networks; Internet Protocol addressing; network analysis; network architecture; network-requirement analysis; network flow analysis; network performance evaluation; network simulation models; statistical models; performance analysis; discrete random variables; continuous random variables; random variable generation; queuing theory; single-server-queues; and multiserver queues.